Replication-Coupled Dilution of H4K20me2 Guides 53BP1 to Pre-replicative Chromatin - Pellegrino, Stefania; Michelena, Jone; Teloni, Federico; Imhof, Ralph; Altmeyer, Matthias (Cell reports (Cambridge), 2017)
The bivalent histone modification reader 53BP1 accumulates around DNA double-strand breaks (DSBs), where it dictates repair pathway choice decisions by limiting DNA end resection. How this function is regulated locally and across the cell cycle to channel repair reactions toward non-homologous end joining (NHEJ) in G1 and promote homology-directed repair (HDR) in S/G2 is insufficiently understood. Here, we show that the ability of 53BP1 to accumulate around DSBs declines as cells progress through S phase and reveal that the inverse relationship between 53BP1 recruitment and replicated chromatin is linked to the replication-coupled dilution of 53BP1’s target mark H4K20me2. Consistently, premature maturation of post-replicative chromatin restores H4K20me2 and rescues 53BP1 accumulation on replicated chromatin. The H4K20me2-mediated chromatin association of 53BP1 thus represents an inbuilt mechanism to distinguish DSBs in pre- versus post-replicative chromatin, allowing for localized repair pathway choice decisions based on the availability of replication-generated template strands for HDR. [Display omitted] •The genome caretaker 53BP1 preferentially marks DSBs in pre-replicative chromatin•Replication-coupled dilution of H4K20me2 restrains 53BP1 function•DSB repair pathway choice is linked to replication status of broken genomic loci•Premature chromatin maturation shifts the balance from HDR to NHEJ activities Pellegrino et al. report how replication-dependent differences in chromatin inform the DNA damage response machinery about the replication status of broken genomic loci. This chromatin-embedded information affects 53BP1 binding and directs the choice of repair pathway used to fix DNA double-strand breaks.